DINAMIKA HUBUNGAN ISLĀM DAN PERADABAN MODERN DALAM PEARADIGMA ALTERNATIVE MODERNITIES - Fitria, Risa Pramita Wilda (Faculty of Da’wa and Islamic Communication, State Institute for Islamic Studies of Syaikh Abdurrahman Siddik Bangka Belitung, 2024)
This research delves into a comprehensive exploration of the dynamics between Islām and modern civilization when viewed through the concept of Alternative Modernities . With the aim of deeply understanding the influence of Islām in the modern world, uncovering the challenges faced by Islām in the contemporary era, and exploring fresh ideas within Islāmic thought related to modernity. Qualitative approaches and literature research are employed to delve into the perspectives of prominent figures such as Nurcholish Madjid, Muhammad Iqbal, and Fazlur Rahman. The findings of this research document the monumental contributions of Islām in politics, economics, and science within modern civilization. However, amidst the tumult of globalization, complex challenges arise, such as controversial interpretations of religious teachings and intense debates on social issues and human rights. Within the framework of Alternative Modernities, Islām offers a perspective of modernity that is not only scientific but also reflects moral values while maintaining the authenticity of religious identity. Reforming Islāmic thought and practices, including creatively adapting to culture and harmoniously integrating religious values with the demands of modernity, become crucial elements in this discussion. This research not only provides profound insights but also enlivens the complexity of the relationship between Islām and modern civilization by recognizing cultural diversity and understanding modernity through a fresh and contextual alternative perspective.